FTA supports the development of Sri Lanka Green Climate Fund Country Program - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
The program presents a set of priority investment areas for Sri Lanka as well as a potential project portfolio over the next 3-5 years.